2021
DOI: 10.1177/10497323211004104
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Interpretation of Metaphors: Exploring Young Adults’ Subjective Experiences With Depression

Abstract: The aim of this study was to provide a cross-cultural exploration of how young adults with depression use metaphors to describe their illness experiences. Data were collected in semi-structured interviews, designed to capture rich and detailed descriptions of participants’ firsthand narrative experiences of depression and how they make sense of depression. Thirty-three participant interview data were analyzed, using a combination of deductive and inductive approaches. The analysis resulted in extracting five m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Third, the findings also reveal that, despite the negative feelings that exist in the complaining and regret narratives, many patients have developed positive sense making of their experiences, including the superiority and discovery narratives, which is different from the findings of a majority of previous studies that mainly found the negative aspects of depression experiences. For instance, Roystonn et al (2021) posited that patients' most common images of depression were darkness, descent, and a weight in the Western society, and they also found that patients in Singapore described their illness experiences with three negative metaphors-depression as affliction, depression as journey (e.g., a long distance race and to the edge of life), and depression as supernatural (e.g., divine punishment). The present study, on the contrary, shows that some patients describe they become depressed because of superior intelligence and/or morality (e.g., prioritizing the demands of others).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the findings also reveal that, despite the negative feelings that exist in the complaining and regret narratives, many patients have developed positive sense making of their experiences, including the superiority and discovery narratives, which is different from the findings of a majority of previous studies that mainly found the negative aspects of depression experiences. For instance, Roystonn et al (2021) posited that patients' most common images of depression were darkness, descent, and a weight in the Western society, and they also found that patients in Singapore described their illness experiences with three negative metaphors-depression as affliction, depression as journey (e.g., a long distance race and to the edge of life), and depression as supernatural (e.g., divine punishment). The present study, on the contrary, shows that some patients describe they become depressed because of superior intelligence and/or morality (e.g., prioritizing the demands of others).…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka (2020) revealed depression-linked beliefs among older adults with depression, which include guilt and regret, pessimism, futility of treatment, and desire to be needed by loved ones and society. Roystonn et al (2021) elaborated on three major themes of depression narratives through examining how young adults with depression use metaphors to describe their illness experiences—depression as affliction, depression as journey, and depression as supernatural.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study that has investigated the cultural differences of metaphors has found significant differences between Thai, Bulgarian, English and Swedish language users in which they have compared 115 different metaphors in these languages (Zlatev et al, 2012). Moreover, metaphor interpretation was subjective for the patients who suffer from depression as well (Roystonn, 2021). Some of the words patients described their illnesses were darkness, a weight, or a bubble (Charteris-Black, 2012).…”
Section: Discussionmentioning
confidence: 99%